Cognitive Skills of Canadian Educators: An Analysis of PIAAC Data - Yildirim Erbasli, Seyma Nur; Cui, Ying (Alberta Journal of Educational Research, 2022)
The purpose of this study was to conduct national and cross-country analyses to provide insights about educator cognitive skills in literacy, numeracy, and problem-solving within Canada and across nineteen countries using the PIAAC data. MANOVA results of profession differences within Canada demonstrated that educators outperformed other professions in general programs, health and welfare, and services but underperformed the professions in science, mathematics, and computing in all three domains. MANOVA results of educator differences across countries showed that educators in Canada outperformed those in Denmark, Estonia, the Russian Federation, and the United Kingdom in literacy, outperformed the United Kingdom in numeracy, and outperformed Denmark, Estonia, and the United Kingdom in problem-solving. Finally, multiple regression analyses identified statistically significant indicators of Canadian educators’ literacy, numeracy, and problem-solving proficiencies. The results of this study reveal and suggest that the cognitive skills of Canadian educators have the potential to be enhanced. Keywords: teacher cognitive skills, literacy, numeracy, problem-solving in technology-rich environments L'objectif de cette étude était de mener des analyses nationales et internationales afin de fournir des informations sur les compétences cognitives des éducateurs en matière de littératie, de numératie et de résolution de problèmes au Canada et dans dix-neuf pays à l'aide des données de l'enquête PIAAC. Les résultats de l'analyse MANOVA des différences entre les professions au Canada ont démontré que les éducateurs surpassent les autres professions dans les domaines des programmes généraux; de la santé et du bien-être; et des services, mais qu'ils sont moins performants que les autres professions en sciences, en mathématiques et en informatique dans les trois domaines. Les résultats de l'analyse MANOVA des différences entre les éducateurs des différents pays ont montré que les éducateurs du Canada surpassent ceux du Danemark, de l'Estonie, de la Fédération de Russie et du Royaume-Uni en littératie, surpassent ceux du Royaume-Uni en numératie et surpassent ceux du Danemark, de l'Estonie et du Royaume-Uni en résolution de problèmes. Enfin, les analyses de régression multiple ont permis d'identifier des indicateurs statistiquement significatifs des compétences des éducateurs canadiens en matière de littératie, de numératie et de résolution de problèmes. Les résultats de cette étude révèlent et suggèrent que les compétences cognitives des éducateurs canadiens ont le potentiel d'être améliorées. Mots clés : compétences cognitives des enseignants, littératie, numératie, résolution de problèmes dans des environnements riches en technologie